Phytophthora Root Rot: Importance of the Disease, Current and Novel Methods of Control - Giachero, María Lorena (2022)
Phytophthora sojae is a pathogen of major agricultural importance, responsible for Phytophthora root rot (PRR) in soybean crops, which can cause significant yield losses each year. The severity of the disease depends on the soybean cultivar, its growth stage at the time of pathogen infection, and the environmental conditions. High soil moisture and temperature around 25–30 °C are favorable conditions for the development of the disease. Consequently, cultural practices are mainly limited to avoiding bad weather (high moisture) during the sowing or to promoting soil drainage. The use of chemical fungicides is restricted to seed treatments when there is a high risk of disease development. Currently the most economical option for controlling P. sojae is the use of host resistance. However, even if breeding is the main control strategy of PRR, the use of resistant cultivars leads to selection pressure on P. sojae populations, which can lead to high variability of the pathogen and therefore to its adaptation to overcome plant resistance. New strategies are therefore needed, including the use of biological control agents (BCAs). The use of BCAs (i.e., microorganisms or their metabolites) is a promising and sustainable alternative to PRR control that should be strengthened. Therefore, this review addresses the P. sojae–soybean interaction, mechanisms of pathogenicity and host resistance, as well as current and new management strategies with emphasis on the biological control of P. sojae and its associated mechanisms